Parafia rzymskokatolicka w Mikaszewiczach w diecezji pińskiej w świetle inwentarza kościoła z 1938 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2018)
Mikaszewicze in Polesie, Poland, developed quite intensely thanks to the construction of the railway, the factory of plywood and the sawmill. This town developed after Poland regained its independence in 1918. The factories which were built there attracted a number of workers, which led to the creation of a fairly large town with a workers' settlement in 1938. Then there was a need to erect a separate parish and, given that the neighbouring villages of Rudnia, Morszczynowicze and Zaprosie accepted the Orthodox faith in the period of Poland’s captivity. Initially, the parish priests from Dawidgródek and Łachwa celebrated church services in private houses and later in the school in Mikaszewicze. In 1923, attempts were made to establish a new pastoral and parish centre. In 1927, the Ordinary of Pińsk erected a parish dedicated to the Queen of the Crown of Poland, and Rev. Paweł Stepak was appointed a parish priest. The church, built in a mixture of Gothic and Romanesque style, was consecrated on 18 July 1937 by Bishop Kazimierz Bukraba.